Will Chinese ICT workers unite? new signs of change in the aftermath of the global economic crisis. (1st October 2010) - ,
Abstract : This paper contextualises and assesses the escalation and evolution of labour activism during the 2008 global economic crisis in China. It argues that both new incentives and new impediments to labour activism have arisen in the midst of broader changes in the labour market, the official trade union, and regional production networks. The recent trend of spatial and technical restructuring of China's ICT sector, as induced simultaneously by capital's self-initiated transformation of the modes of accumulation and by the governmental need to sustain China's economic growth, is likely to generate a sizeable reshuffling of labour markets and to reconstitute working-class experiences across regional, industrial, and educational segmentations.